Characteristics of quince fruits cultivars' (Cydonia Oblonga Mill.) grown in Brazil - Leonel, Magali [UNESP]; Leonel, Sarita [UNESP]; Tecchio, Marco António [UNESP]; Mischan, Martha Maria [UNESP]; Moura, Mara Fernandes; Xavier, Diego (Southern Cross Publishing, 2016)
The fruits of quinces are mostly used to produce food and functional products. Studies on this fruit have increased recently aiming to increase the use of quince fruit as industrial raw material. The present study aimed to evaluate ten different cultivars of quince grown in São Paulo state, Brazil, regarding weight, transverse and longitudinal diameter, skin and pulp color, firmness, pH, acidity, moisture, ash, starch, lipids, fiber and total sugars of fruits, aiming to provide important information to the industrial applicability. Significant differences were observed between the cultivars for the analyzed parameters. The relationship between transverse and longitudinal diameters of fruits showed mainly globular shape. Analyzing the firmness of the fruits' pulp it was observed semi-hard pulp. The fruits analyzed were appropriate for consumption and have potential for application in industrial processing.
Keywords: Color; Cydonia oblonga mill; Firmness; Nutritional composition; Weight